Choosing Wisely in Healthcare Epidemiology and Antimicrobial Stewardship. (28th March 2016) - Morgan, Daniel J.; Croft, Lindsay D.; Deloney, Valerie; Popovich, Kyle J.; Crnich, Chris; Srinivasan, Arjun; Fishman, Neil O.; Bryant, Kristina; Cosgrove, Sara E.; Leekha, Surbhi
Abstract : OBJECTIVE: To identify Choosing Wisely items for the American Board of Internal Medicine Foundation. METHODS: The Society for Healthcare Epidemiology of America (SHEA) elicited potential items from a hospital epidemiology listserv, SHEA committee members, and a SHEA–Infectious Diseases Society of America compendium with SHEA Research Network members ranking items by Delphi method voting. The SHEA Guidelines Committee reviewed the top 10 items for appropriateness for Choosing Wisely. Five final recommendations were approved via individual member vote by committees and the SHEA Board. RESULTS: Ninety-six items were proposed by 87 listserv members and 99 SHEA committee members. Top 40 items were ranked by 24 committee members and 64 of 226 SHEA Research Network members. The 5 final recommendations follow: 1. Don't continue antibiotics beyond 72 hours in hospitalized patients unless patient has clear evidence of infection. 2. Avoid invasive devices (including central venous catheters, endotracheal tubes, and urinary catheters)and, if required, use no longer than necessary. They pose a major risk for infections. 3. Don't perform urinalysis, urine culture, blood culture, or Clostridium difficile testing unless patients have signs or symptoms of infection. Tests can be falsely positive leading to overdiagnosis and overtreatment. 4. Do not use antibiotics in patients with recent C. difficile without convincing evidence of need. Antibiotics pose a high risk of C. difficile recurrence. 5. Don't continue surgical prophylactic antibiotics after the patient has left the operating room. Five runner-up recommendations are included. CONCLUSIONS: These 5 SHEA Choosing Wisely and 5 runner-up items limit medical overuse. Infect Control Hosp Epidemiol 2016;37:755–760